American Poetry : The Nineteenth Century. Volume one, Philip Freneau to Walt Whitman - Library of America (Firm) (New York : Library of America, 1993)
Included in the anthology is newly researched biographical sketches of each poet, a year-by-year chronology of poets and poetry from 1800-1900, and extensive notes.
Includes bibliographical references and indexes.
Wilson's Senior High School, November 2002
Wilson's Public Library, May 1995
Booklist
Young Adult
Keywords: American poetry -- 19th century